Pengaruh Perbedaan Kombinasi Basis Hidrokarbon Terhadap Karakteristik Fisik Sediaan Salep Ekstrak Etanolik Daun Binahong (Anredera cordifolia(Ten.) Steenis): Pengaruh Perbedaan Kombinasi Basis Hidrokarbon Terhadap Karakteristik Fisik Sediaan Salep Ekstrak Etanolik Daun Binahong (Anredera cordifolia(Ten.) Steenis) - Sisca Devi; Ifka Perdana Putri (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
The skin is the most important organ in protection against injury and pathogens. One of the skin disorders in the form of burns. The binahong plant has flavonoid compounds, saponins and oleanolic acid which are efficacious as anti-inflammatory and reduce pain in burns. The selection of the right ointment base greatly affects the therapeutic effect of the ointment. This study aims to determine the effect of different combinations of hydrocarbon bases on the physical characteristics of the ethanolic extract of binahong (Anredera cordifolia (Ten.) Steenis) ointment preparations. This type of research is experimental with a completely randomized design (CRD). Extraction using maceration method with 70% ethanol. The hydrocarbon bases are 5% cera flava, 10% liquid paraffin, and 24% Vaseline album. The physical characteristics of organoleptic test, homogeneity, pH, protective power were analyzed descriptively. Adhesion, dispersion, viscosity were tested for normality and homogeneity using the Shapiro Wilk test and Levene's test. Normal and homogeneous distributed data were tested with one-way ANOVA with 95% confidence level followed by the Tuckey test. The combination of hydrocarbon bases affects the physical characteristics of the ethanolic extract of binahong leaf ointment, including viscosity, spreadability, and adhesion. The test results of organoleptic, homogeneity, pH met the requirements. The test of adhesion, dispersibility and viscosity, with a significance of p<0.05, had a significant difference between each formula.